Immunological mechanisms underlying chronic rhinosinusitis with nasal polyps. (2nd September 2018) - Heffler, Enrico; Malvezzi, Luca; Boita, Monica; Brussino, Luisa; De Virgilio, Armando; Ferrando, Matteo; Puggioni, Francesca; Racca, Francesca; Stomeo, Niccolò; Spriano, Giuseppe; Canonica, Giorgio Walter
ABSTRACT: Introduction : Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common and quality-of-life impacting disorder, with an underlying immunological mechanism similar to other conditions such as eosinophilic asthma or atopic eczema. Areas covered : This review article summarizes the most recent evidence on the main immunological mechanisms involved in the pathogenesis and the perpetuation of CRSwNP, with a particular focus on the key role of epithelium-derived inflammation as a consequence of the interaction with the airborne environment. Expert commentary : The increase in knowledge of the immunology of CRSwNP leads to the development of therapeutical strategies based upon the use of biologic agents that, according to a personalized and precision medicine approach, will provide each single patient with the most suitable immunological treatment.